PERAN WORLD WIDE FUND FOR NATURE (WWF) TERHADAP UPAYA PENYELAMATAN KERUSAKAN IKLIM DI PROVINSI RIAU STUDI KASUS: EARTH HOUR - Ulfa Apriliana Lutfi; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The purpose of this study was to determine the role of the World Wide Fund for Nature (WWF) and the involvement of Earth Hour in efforts to save climate damage, especially in Riau Province. Earth is facing a serious threat due to extreme climate change triggered by human activities that are not environmentally friendly. The natural crisis triggers the emergence of the role of various actors other than the state or commonly referred to as Non-Governmental Organizations (NGOs), one of which is WWF which in this study was carried out in the WWF working area of Central Sumatra. This study uses a constructivist perspective and is guided by the Role theory and the concept of the Global Civil Society. The method used is a qualitative method with data collection techniques including interviews and literature studies from several journals, books, documents, and websites.This research shows WWF's ability to save the environmental and climate conditions in Riau Province by running programs related to conservation, restoration, mitigation, and rehabilitation. Earth Hour Pekanbaru has been operating since 2013, until now it has become a community of young people who fight for change. Earth Hour Pekanbaru helped campaign for WWF Central Sumatra programs, especially on energy issues and climate change. The results of this study conclude that WWF has a great role and capability in mitigating climate damage. WWF carries out environmental missions with many of its partners including Earth Hour and sparks global conversations and generates civil society movements to save Earth's future. Keywords: Role, NGO, WWF, WWF Central Sumatra, Earth Hour, Climate Damage, Riau Province.